Analisis Kebijakan Pembiayaan Porsi Haji pada Pegadaian Syariah: Tinjauan dari Aspek Regulasi dan Prinsip Syariah - Ocha Pratika; Ahmad Perdana Indra; Tuti Anggraini (Indonesian Journal of Islamic Economics and Business, 2026)
This study aims to analyze the Hajj portion financing policy at Pegadaian Syariah from a regulatory and sharia perspective. The Hajj pilgrimage requires istitha'ah (ability), but in practice, not all people are financially prepared to meet the initial BPIH (Islamic Pillars of Hajj) deposit. This situation encourages the emergence of rahn-based financing with gold as an alternative solution. This study uses a normative juridical method with a qualitative approach through analysis of literature, regulations, and field data. The results show that Hajj portion financing has a strong legal basis through the DSN-MUI Fatwa on rahn and gold rahn, and is reinforced by MUI Fatwa No. 004 of 2020, which permits financing of the initial Hajj deposit as long as it complies with sharia principles. This scheme is considered more in line with the principle of prudence because it is supported by real assets. From a sharia perspective, this financing provides benefits in the form of easy access for the public to obtain Hajj portion numbers amidst the long queues. However, there is a potential shift in the meaning of istitha'ah because financial capability does not entirely stem from independent readiness. Therefore, its implementation must continue to adhere to the principles of prudence, repayment capacity, and freedom from usury. Going forward, adjustments to collateral values ​​are needed to make them more proportional and regulations must be strengthened to maintain alignment with the maqasid of sharia.